Developing the Deep : evaluating the feasibility of establishing a recreational diving sector in the Ísafjarðardjup area of Iceland - Deverell, Alan (2011)
One of the main goals of coastal zone management is to encourage the sustainable and integrated use of an area’s natural resources. Some activities lend themselves more readily to these objectives than others. Marine based tourism is one of them, and in particular recreational diving, one of the world’s fastest growing sports. The Westfjords of Iceland, with its unique coastline, rich biota and long maritime heritage, appears to have all the potential to be an excellent diving destination. Yet, it suffers from its remoteness, basic infrastructure and lack of tourism development . This thesis looks at the possibilities for establishing a thriving recreational diving sector in the area around Ísafjarðardjup that would provide a number of new opportunities for the tourist industry, as well as support for marine-based research and education. It proposes a development model based on close collaboration between these sectors and uses data from a number of surveys that provide information on visitor characteristics and preferences. The thesis concludes that while the establishment of a successful diving sector is possible, this will depend upon developing a clear and integrated tourism policy for the region and providing adequate support to the businesses and associations involved. Atvinnuþróunarfélag Vestfjarða